2018
DOI: 10.21608/edj.2018.79172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Versus Transparent Matrices on Proximal Contact Tightness of Class Ii Bulk-Fill Composite Restorations

Abstract: Purpose: This study investigated the effect of metal versus transparent matrix systems on proximal contact tightness (PCT) of class II bulk-fill composite resin restorations.Methods: 80 Ivorine teeth with standardized MO cavity preparations were randomly divided into 4 equal groups (n=20). Group1; sectional metal matrix, group2; pre-contoured circumferential metal matrix in a Tofflemire retainer, group3; conventional metal matrix in a Tofflemire retainer, and group4; Blue Cure-Thru transparent contoured matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Whereas, dead-soft matrix due to matrix deformation, sometimes produced negative contour of the proximal area. Further, El-Shamy[ 14 ] also has shown that proper PCT for bulk-fill composite restorations can be produced by sectional metal matrix rather than transparent matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, dead-soft matrix due to matrix deformation, sometimes produced negative contour of the proximal area. Further, El-Shamy[ 14 ] also has shown that proper PCT for bulk-fill composite restorations can be produced by sectional metal matrix rather than transparent matrix.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] in a study comparing different techniques for establishing proximal contacts in posterior composite restoration concluded that there was no difference in the technique used. El-Shamy[ 14 ] compared metal versus transparent matrices and found that sectional metal matrices produced proper PCT. There is a need to examine the literature on various matrix systems used for establishment of proper proximal contacts.…”
Section: Introductionmentioning
confidence: 99%